Per un teatro trans (-disciplinare e -culturale): Un caso di filosofia al lavoro, che sembra danza - Attisani, Antonio (Mimesis Journal, 2017)
This article is devoted at first to a book which collects the proceedings of an important Italian symposium concerning the theurapetic implementation of theatre protocols, and then to the Batsheva Dance Company. The ensemble leaded by Ohad Naharin is presented as a combination of singular biographies, and the analysis of its genuine theatre is proposed side by side with Embodied Philosophy in Dance, the essay by Einav Katan that among others inaugurate a new theatrology.